2021
DOI: 10.1007/s10608-021-10253-1
|View full text |Cite
|
Sign up to set email alerts
|

Are Acute Increases and Variability in Emotion Regulation Strategies Related to Negative Affect and Paranoid Thoughts in Daily Life?

Abstract: Background Negative affect reliably predicts paranoid thoughts. Previous studies point to the importance of emotion regulation for paranoid thoughts but have not yet focused on effects of acute increases and variability in strategy use. Methods We conducted an experience-sampling study for one week in a subclinical sample. Acute increases in the intensity of strategy use from one measurement point until the next, between-strategy variability (i.e., standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Paranoid thoughts are associated with a lower quality of life (Watson et al, 2018), lower psychological well-being (Freeman et al, 2014), and negative affectivity (Bahlinger et al, 2021).…”
Section: şAhin and Derin Quest For Significance And Psychological Sym...mentioning
confidence: 99%
“…Paranoid thoughts are associated with a lower quality of life (Watson et al, 2018), lower psychological well-being (Freeman et al, 2014), and negative affectivity (Bahlinger et al, 2021).…”
Section: şAhin and Derin Quest For Significance And Psychological Sym...mentioning
confidence: 99%
“…However, a few studies find that between‐ERV is not associated with well‐being (Bahlinger, Lincoln & Clamor, 2022; Elkjaer et al ., 2022). Similar mixed findings are evident for within‐ERV, with one study reporting a link between within‐ERV and reduced well‐being (Elkjaer et al ., 2022), while others find a connection between within‐ERV and increased well‐being (Wang et al ., 2021; Wenzel et al ., 2022), and yet again others find no relationship between within‐ERV and well‐being (Bahlinger et al ., 2022; Battaglini et al ., 2022). Lastly, concerning ERD, two studies failed to find consistent associations between ERD and well‐being (Elkjaer et al ., 2022; Wenzel et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to between‐ERV, some studies indicate that between‐ERV is associated with better mental health outcomes including fewer symptoms of depression (Wang, Blain, Meng, Liu & Qiu, 2021) and less negative affect (Battaglini, Rnic, Jameson, Jopling, Albert & LeMoult, 2022; Blanke et al ., 2020; Wang et al ., 2021; Wenzel, Blanke, Rowland & Kubiak, 2022). However, a few studies find that between‐ERV is not associated with well‐being (Bahlinger, Lincoln & Clamor, 2022; Elkjaer et al ., 2022). Similar mixed findings are evident for within‐ERV, with one study reporting a link between within‐ERV and reduced well‐being (Elkjaer et al ., 2022), while others find a connection between within‐ERV and increased well‐being (Wang et al ., 2021; Wenzel et al ., 2022), and yet again others find no relationship between within‐ERV and well‐being (Bahlinger et al ., 2022; Battaglini et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…ESM studies in psychosis revealed that patients with psychosis reported higher efforts in regulating emotions and used more strategies than healthy controls in the flow of daily life (Ludwig et al, 2020a;Raugh and Strauss, 2021;Visser et al, 2018). In early psychosis, increased use of acceptance and reappraisal predicted lower negative affect at the following timepoint, while increased use of rumination and suppression was associated with higher negative affect (Bahlinger et al, 2021). ESM thus makes it possible to examine how the use of different ER strategies unfolds in the context of daily life in psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…The very few studies that investigated ER usage in psychosis (Bahlinger et al, 2021;Visser et al, 2018) did not take context into account.…”
Section: Introductionmentioning
confidence: 99%